ASPEK AFEKTIF HASIL PEMBELAJARAN MATEMATIKA - Suryanto, Suryanto (PAEDAGOGIA, 2008)
Teachers and parents often complain about the negative affect of students onmathematics learning at schools, but there has been no official report on this matter. Thisstudy was intended to investigate the status of the affective aspect of the result of theschools mathematics education. The affects measured were attitude, interest, motivation,anxiety, self-concept, extrinsic appreciation, intrinsic appreciation, operational appreciation,belief about mathematics, belief about self, belief about mathematics teaching,and belief about social context. The subjects were the first year students of the Faculty ofMathematics and Sciences of the State University of Yogyakarta (UNY) comprisingstudents of eight departments i.e. Department of: Biology, Biology Education, Chemistry,Chemistry Education, Mathematics, Mathematics Education, Physics, and PhysicsEducation. The instrument was adapted from the affective test items developed byWilsonused in the National Longitudinal Study on Mathematics Achievement by the SchoolMathematics Study Group in the USA, and supplemented by test items on beliefsdeveloped based on the McLeod’s classification. The data indicated that the affects wereof either low level or neutral level (neither favorable nor unfavorable for mathematicslesson) except for the belief about mathematics, about mathematics teaching, and aboutsocial context of mathematics.